CHILD CARE POLICY: PROTECTING CHILDREN FROM ABUSE, NEGLECT AND EXPLOITATION - Gunawan Widjaja (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
The Child Care Policy is a series of measures and rules established by the government and relevant stakeholders, which aim to protect children's rights, ensure their safety, and prevent acts of violence, neglect, and exploitation against children. This policy includes prevention, protection, and case handling efforts, and aims to create a safe and supportive environment for children's growth and development. Thus, the Child Care Policy is an important initiative that aims to protect children from abuse, neglect and exploitation. With effective implementation, the Child Care Policy is expected to significantly reduce cases of child abuse, neglect and exploitation, and contribute to the formation of a better future generation.